ANALISIS RANCANGAN PROGRAM PEMBERIAN ASI EKSKLUSIF MELALUI STRATEGI PEMASARAN SOSIAL DI PUSKESMAS PADANGSARI SEMARANG 2017 - Aini Nur Santi; Septo Pawelas Arso; Chriswardani Suryawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
In Indonesia, Infant Mortality Rate reaches 22 per 1,000 live births. Exclusive breastfeeding is one of the absolute efforts to reduce factors of infant mortality. Puskesmas Padangsari as Community Health Center has exclusive breastfeeding 59.79% coverage, it is still below the normal line. The goal for researchers is creating breastfeeding program planning, identify environmental factors both internally and externally in Puskesmas Padangsari then formulate a strategy. The methods which researchers use are qualitative with exploratory study approaches. The results of this research for internal factors are the projection of the strengths and weaknesses of their resource caused by two midwives and one nutritionist, outreach and counselling activities, the flowing funds and there are proponents of media promotion yet unfortunately it is not supported with rooms etc. As opportunities and threats, external factors include clinics have cadres, constraints on communications outreach as well as the perceptions of breastfeeding is not appropriate and not accompanied by the implementation of the target response etc. The results of the analysis situation for Puskemas Padangsari is resulted in position of quadrant strategy of  "aggressive" which indicates that the Organization has the power and opportunities where these advantages in supporting the policy of the organization grew more aggressively. An alternative strategy that can be applied to Puskesmas Padangsari is a social marketing campaign. These campaigns help increase the acceptance of the idea of social or behavioral change without coercion, volunteering and awareness of self.